Manajemen Pondok Pesantren Asy-syamsiyah Denpasar Bali (Kompetensi Guru dan Bimbingan Potensi Santri) - Muhsin, Hafidul; Atmaja, Nengah Bawa; Dantes, Nyoman (Universitas Pendidikan Ganesha, 2017)
The research aims to determine the strategy used Pondok Pesantren Asy-Syamsiyah in overcoming the problems that exist, to determine the increase in knowledge management systems and skills of teachers Pondok Pesantren Asy-Syamsiyah, to determine the role of Ash-Syamsiyah boarding school in guidance santri. This study uses qualitative research. The data obtained in this research through direct observation of researchers examine and follow the activities at the Pondok Pesantren As-Syamsiyah Denpasar Bali, interview the researchers interviewed teachers, administrators, and students is in boarding school, from books to documents in the administration there in the office, photos and other documents. The study yielded that the competency of teachers is lacking with the lack of training and education boarding school teachers, teachers who lack formal education can affect theÂ management manage. In developing the potential of students, teachers provide training in accordance with the talents of students outside of active learning.